Application Of The Pari Passu Clause In PT PLN Loan Restructuring - Grace Ester Mercedes; Sylvia Veronica Siregar (Peneliti.net, 2023)
As a state-owned public utility, Perusahaan Listrik Negara (PLN) is crucial to Indonesia's provision of energy. The debt contractual agreement becomes a reference in the context of restructuring, and for that reason, the written terms have a significant impact. The pari passu provision is among the most significant parts of the contract. However, as of right now, PLN is still using the ratable payments to creditors idea rather than the pari passu concept that has been modified by the IMF. By demonstrating the demands of the organization and the effects of applying the idea, the research aims to demonstrate methods to implement a new concept. It offers findings on how to implement the new pari passu idea, which is comprehensive and applicable to PT PLN, by applying Kotter's 8-Step Change Model technique.